Engenharia da qualidade: aplicação da ferramenta FMEA em uma fábrica de gelatos localizada em Caicó-RN - Silva, Erica Vanessa Fernandes da (Universidade Federal Rural do Semi-Árido, 2019)
The pursuit of greater productivity is one of the most desired points within any company. In this context, This paper is intended to apply the FMEA method (Failure Mode and Effect Analysis), in a gelato factory located in the city of Caicó - RN. Due to its economic and strategic importance, decided to analyze the process of manufacturing popsicles. Therefore, a case study was conducted, where through observation and informal interviews with the manager and staff, it was possible to perform the process mapping. From this we identified the most critical steps to assign severity indexes, occurrence and detection of integral parts of the process, and thus calculate the NPR (priority risk number). The following problems were encountered: Lack of standardization (NPR = 60/96), Freezing operation problems (NPR = 140), Packaging operation problems (NPR = 72), Storage (NPR = 84) and Misuse of EPI's (NPR = 126). Finally, mitigating measures for the reality found were suggested, as well as propositions for future work. Due to its characteristics, the research is classified as exploratory, descriptive, applied, quantitative with a case study. From this purpose, the present work aims to analyze the failure modes and their effects on the processing of popsicle in a gelato factory, located in Caicó-RN through FMEA tool, where it was inserted in a continuous improvement approach. quality in popsicle processing.
Artigo
Keywords: Gestão da qualidade; Ferramentas da qualidade; FMEA; Quality management; Quality tools; FMEA; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA